Pelatihan Penguatan Peran Badan Permusyawaratan Rakyat Nagari (BPRN) dalam Mendukung Penyelenggaraan Pemerintahan Nagari di Nagari Sumanik Kabupaten Tanah Datar - Ria Ariany; Desna Aromatica; Hendri Koeswara; Ilham Aldelano Azre; Kusdarini Kusdarini; Muhammad Ichsan Kabullah; Misnar Sitriwanti; Roni Ekha Putera; Rozidateno P Hanida; Syamsurizaldi Syamsurizaldi; Wewen Kusumi Rahayu; Yoserizal Yoserizal (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2019)
After the enactment of the Village Law which is full of various new policies, it also has implications for the Village Consultative Body (BPD) with changes in the position, duties, functions and authority of the BPD. One of them is the issuance of Permendagri No. 110/2016 concerning BPD, and most recently in the context of West Sumatra the issuance of the Regional Regulation of West Sumatra Province No 7/2018 concerning Nagari. This Perda is claimed to be the first indigenous village regulation in Indonesia that wants to show the existence of Nagari